(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
In this paper we investigate the impact of three presentation formats of textual multisemiotic information in the comprehension of written texts from a rhetorical passage of the genre Monetary Policy Report (MPR). To do this, an experiment with three comprehension tests was designed, in which texts varied in the constituent multisemiotic preponderance: (A) original text, (B) text with predominance of the graphic system, and (C) text with predominance of the verbal system. These instruments were applied to 151 students at a university program in the field of Economics in Chile. They were divided into two groups: (1) university freshmen and (2)university third graders. The results indicate, on the one hand, that there are no statistically significant differences between the three conditions of the comprehension tests, in each group of students (Group 1 and Group 2). On the other hand, there are significant differences between the results of the reading comprehension tests of first and third year university students, particularly, in favor of texts predominantly of one information encoding format (verbal or graphic); while there is no difference in terms of the disciplinary university level in texts that required an integrated reading of verbal and graphic codes. Implications of these results for the comprehension of multisemiotic specialized texts are discussed.